Rekrutmen Perangkat Desa di Desa Blumbungan Kecamatan Larangan Kabupaten Pamekasan - Mila Agustini; Abubakar Basyarahil (Universitas Sultan Ageng Tirtayasa, 2022)
Village officials have an important role in village development and welfare. The implementation of village apparatus recruitment is the first step for village officials in their involvement with village government so that a recruitment process is needed in its implementation. There are various problem in the implementation of village apparatus recruitment, such as lack of planning, lack of information, to indications of nepotism practices that have become public secrets in the community. Through the recruitment process that has been proposed by Simamora (2020) which consists of recruitment planning, recruitmen strategy, recruitment sources, screening, and gathering of applicant, the village apparatus recruitment process in Blumbungan Village, Larangan District, Pamekasan Regency is reviewed. The result of a qualitative research study based on indicators of the recruitment process according to Simamora (2020) The Blumbungan Village Government does not carry out all the indicators of the recruitment process. In the future, The Blumbungan Village Government needs to implement a recruitment process starting from recruitment planning, recruitment strategic, recruitment sources, screening, to collection of applicant.